Effect of different Rugby League warm ups on performance and perceptions of readiness to perform - Pringle, F. A.; Sealey, R. M.; Sinclair, W. H.; Bowman, P. W. (Journal of Australian Strength and Conditioning, 2013)
The objective of this study was to determine whether a dynamic-based warm up of shorter duration and higher intensity (DSH) was more effective at preparing elite rugby league players for performance, than a warm up that included combined static and dynamic activities of longer duration and lower intensity (CLL). Elite rugby league players (n=28) completed the warm up routines in random order, separated by 7 days. Following each warm up, players completed vertical jump and 40 m sprint assessments. The DSH warm up was significantly shorter in duration (DSH: 16 ± 1 min vs CLL: 22 ± 1 min, p = 0.013) and higher in intensity (average heart rate: DSH: 122 ± 14 bpm vs CLL: 115 ± 11 bpm, p = 0.009) than the CLL warm up. The DSH warm up resulted in significantly faster 40 m sprint time (DSH: 5.26 ± 0.13 s vs CLL: 5.34 ± 0.22 s, p = 0.033) with no difference in vertical jump (DSH: 0.59 ± 0.05 m vs CLL: 0.6 ± 0.05 m), 10 m (DSH: 1.63 ± 0.05 s vs CLL: 1.67 ± 0.09s) and 20 m (DSH: 2.91 ± 0.06 vs CLL: 2.95 ± 0.12 s) sprint time. After using the DSH warm up in three pre-season trial games, players and coaches rated the DSH warm up significantly better at preparing players for performance (DSH: 7.6 ± 1.3 vs CLL: 6.0 ± 1.1, p = 0.019). In conclusion this study unveiled contrasting evidence for the use of a DSH warm up and requires further investigation.